Development of a portable tri-axial seismograph - Azlan Adnan; Nor Azizi Yusoff; Yong, Wee Siang; Ng, Kok Keang; Malaysian Science and Technology Congress (2000 : Genting Highlands, Pahang) (Skudai : Universiti Teknologi Malaysia, 2000)
08